2017
DOI: 10.2147/jpr.s135081
|View full text |Cite
|
Sign up to set email alerts
|

Forced exercise attenuates neuropathic pain in chronic constriction injury of male rat: an investigation of oxidative stress and inflammation

Abstract: Background and objectiveInitial peripheral/central nerve injuries, such as chronic constriction injury (CCI)/spinal cord injury, are often compounded by secondary mechanisms, including inflammation and oxidative stress, which may lead to chronic neuropathic pain characterized by hyperalgesia or allodynia. On the other hand, exercise as a behavioral and non-pharmacological treatment has been shown to alleviate chronic neuropathic pain. Therefore, this study was conducted to examine whether or not exercise reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 73 publications
6
38
0
Order By: Relevance
“…Our results revealed that CCI leads to mechanical allodynia and thermal hyperalgesia, consistent with findings from our previous study 6 . Spirulina microalgae significantly reduced CCI-induced neuropathic pain.…”
Section: Hypoalgesic Effectssupporting
confidence: 93%
See 4 more Smart Citations
“…Our results revealed that CCI leads to mechanical allodynia and thermal hyperalgesia, consistent with findings from our previous study 6 . Spirulina microalgae significantly reduced CCI-induced neuropathic pain.…”
Section: Hypoalgesic Effectssupporting
confidence: 93%
“…Nisha Patro et al reported that oral use of Spirulina alleviates arthritis pain through suppressing inflammatory processes and microglial activation in the spinal cord 36 . Previously, we reported that inflammatory mediator release due to CCI is one of the main mechanisms leading to neuropathic pain 6 . Consistent with the studies which suggest an anti inflammatory property for Spirulina and its content Cphycocyanin 17,37,38 , it is possible that in the present study Spirulina led to analgesia through suppressing inflammatory mediators.…”
Section: Hypoalgesic Effectsmentioning
confidence: 99%
See 3 more Smart Citations